The construction of super-tough polylactide/crosslinked polyamide blends by dynamic vulcanization. (August 2022) - Lu, Zifeng; Wang, Xiangyu; Jia, Shiling; Zhao, Ling; Wang, Zepeng; Han, Lijing; Pan, Hongwei; Zhang, Huiliang; Dong, Lisong
Highlights: With the presence of hexamethylene diisocyanate (HDI) as a crosslink agent, crosslinked hydrogenated C36 dimer acid (HAD)-based polyamide (HPA) and the reactive compatibilization between PLA and HPA are established during the melt blending. From the FTIR spectra and 1 H NMR analysis, the occurrence of soluble linear PLA-HPA copolymer lead to the below estimated values of gel content. The reaction compatibilization also appears by the terminal groups of PLA reacting with the terminal -NCO groups of crosslinked or linear polyamide, and the PLA-HPA copolymer comes into existence. When the content of incorporated HPA up to 20 wt% or above, benefited from the genuine continuous HPA network-like morphology, meanwhile, elongation-at-break exceeding 400% and an equilibrium Izod impact strength over 128 kJ/m 2 . Graphical abstract: Image, graphical abstract Abstract: To overcome the inherent brittleness of polylactide (PLA), a dynamic vulcanization toughening method is adopted in this study. With the presence of hexamethylene diisocyanate (HDI) as a crosslink agent, crosslinked hydrogenated C36 dimer acid (HDA)-based polyamide (HPA) and the reactive compatibilization between PLA and HPA are established during the melt blending. The coalescence of HPA led to the formation of different phase morphologies of the PLA/HPA blends, including "island-sea", "quasi-co-continuous" and "co-continuous" structures. With HAP content of more than 20 wt%, benefited from the genuine continuous HPA network-like morphology, meanwhile, the elongation-at-break exceeding 400% and an equilibrium Izod impact strength over 128 kJ/m 2 . Thus, this work provides a feasible strategy for preparing super-tough PLA-based blends, which can be potentially used in wide industrial applications.